1991
DOI: 10.3759/tropics.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distributions of Wind-dispersed Fruits and Trees of Swintonia schwenkii (Anacardiaceae) in a Tropical Forest of West Sumatra.

Abstract: The mature ftuits are 2 g in fresh weight, having five wings 6Xl cm in size and one seed inside. In contrast with the distribution of seedlings and small trees, many fruits dropped under the crowns of mother trees. The number of fruits decreased exponentially with distance from a mother tree, and ftuits dispersed further than 50 m were rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Number of individuals and m*/m index (Iwao, 1977) (Mukhtar et al,1992). We found that the emergent dominant Swintonia schwenkii showed a clear negative correlation between adult rees and seedlings (Suzuki & Kohyama, 1991). Again inSwintonia population, the bimodality in size distribution was more obvious in the Pinang Pinang Plot (Fig.…”
Section: Grewiafloridamentioning
confidence: 73%
See 1 more Smart Citation
“…Number of individuals and m*/m index (Iwao, 1977) (Mukhtar et al,1992). We found that the emergent dominant Swintonia schwenkii showed a clear negative correlation between adult rees and seedlings (Suzuki & Kohyama, 1991). Again inSwintonia population, the bimodality in size distribution was more obvious in the Pinang Pinang Plot (Fig.…”
Section: Grewiafloridamentioning
confidence: 73%
“…590-635 m) in the Ulu Gadut area, the basin of Sungei (River) Gadut Gadang, 18 km east from Padang, West Sumatra; for detailed description of the sites see Kohyama et al (1986), Suzuki & Kohyama (1991) and Mukhtar et al (1992). The The census for seedlings and saplings was carried out by tagging numbered tapes, measuring of top height and dbh (when taller than 1.3 m), and mapping the position of the stem base.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals of C. cf. dourattri in 0-4 m height classes were gathered under and around the crowns of mother trees, contrasting to small individuals of S. schwenkii which were fewer under the crowns of the mother tress than around them in the same plot (Suzuki & Kohyama, 1991). A few individuals of C. cf.…”
Section: Resultsmentioning
confidence: 96%
“…When thbse poles at a clump could be assumed to be offsprings of the same grandmother as four mother trees, the area could be furthermore limited to the southern part of the estimated area by zoning 10-50 m distance from this clump (Fig. 1 (Suzuki & Kohyama, 1991). When we compare them at the matured fruit stage for Calophyllum cf.…”
Section: Discussionmentioning
confidence: 99%
“…We have monitored the population dynamics of major species at two I-ha permanent plots of a foothill rain forest in Ulu Gadut, West Sumatra since 1980. Spatial distribution patterns of major species in this forest have been revealed and their regeneration mechanisms were discussed with demographic data (Suzuki & Kohyama, 1991; Mukhtar et aZ., 1992; Kohyama et aZ., 1994). This study follows the previous paper (Mukhtar et al, 1992) this cohort population in terms of rates of growth, recruitment and mortality.…”
mentioning
confidence: 99%